Phase II study of cetuximab plus S-1/cisplatin therapy in Japanese patients with advanced gastric cancer. (10th February 2021) - Yamaguchi, Kensei; Fuse, Nozomu; Komatsu, Yoshito; Fujii, Hirofumi; Hironaka, Shuichi; Omuro, Yasushi; Muro, Kei; Yasui, Hirofumi; Ueda, Shinya; Nishina, Tomohiro; Watanabe, Morihiro; Ohtsu, Atsushi
Abstract: Objective: We evaluated the efficacy and safety of first-line S-1 plus cisplatin in combination with cetuximab for Japanese patients with advanced gastric cancer, including gastroesophageal junction adenocarcinoma. Methods: This open-label, single arm, multicenter, phase 2 trial was conducted to assess first-line cetuximab plus S-1 plus cisplatin for advanced gastric cancer. A total of 40 patients from 10 centers were enrolled. Cetuximab was administered weekly, with the initial infusion at 400 mg/m 2 and then 250 mg/m 2 each subsequent week. S-1 plus cisplatin chemotherapy was concomitantly conducted in a 5-week cycle: S-1 (40–60 mg, adjusted for body surface area) was given twice daily for 3 consecutive weeks, followed by a 2-week rest period, and cisplatin (60 mg/m 2 ) was given on day 8 of each cycle for a maximum of 8 cycles. Treatment continued until the occurrence of radiographically confirmed progressive disease, unacceptable toxicity or withdrawal of consent. The primary endpoint was the best overall response. Secondary endpoints included progression-free survival and safety. Results: A total of 40 patients were evaluable. One patient (2.5%) had a complete response; 15 patients (37.5%) had a partial response. The observed overall response rate according to the independent review committee was 40.0% (95% confidence interval, 24.9–56.7; P  = 0.7043 [one-sided null hypothesis: overall response rate ≤ 43%]); median PFS was 5.6 months (95% confidence intervals, 4.2–8.3). No adverse events leading to death were reported during the study, and no specific safety concerns were observed. Conclusions: Overall, the addition of cetuximab to S-1 plus cisplatin was well tolerated in patients with advanced gastric cancer but provided no additional clinical benefit in this study. ClinicalTrials.gov identifier: NCT01388790. Abstract : Adding cetuximab to first-line S-1 plus cisplatin was well tolerated in Japanese patients with advanced gastric cancer but provided no additional clinical benefit versus S-1 plus cisplatin without cetuximab.